Management of company finance - Samuels, J. M. 1938- (International Thomson Business Press, 1996)
This book is about: The financial environment; Flow of funds and taxation; Finance and accounting; Investment appraisal; Capital rationing ans risk analysis in imperfect capital markets; ...